Encyclopedia of American poetry : the nineteenth century - Haralson, Eric L. (Chicago : Fitzroy Dearborn Publishers, 1998)
Contains 115 alphabetically arranged entries that provide in-depth accounts of the lives, writings, and other achievements of nineteenth-century poets, and includes topical essays on nineteenth-century versions of American Indian poetry, popular poetry, songs and ballads, and spirituals.
Includes bibliographical references and indexes.
Booklist.
Library Journal.
Wilson's Senior High School.
Adult.
Adult
Keywords: American poetry -- 19th century; American poetry -- 1800-1899 (19th century)